Emotive Function Used in L'Oreal Paris Advertisements - Ni Made Sutariani; IGA Vina Widiadnya Putri; Ni Nyoman Deni Ariyaningsih (ID Solutions, 2021)
This study aimed at analyzing the occurrence of emotive function used in transcript of ten L’Oreal Paris advertisements videos. In addition, it also intended to analyze the elements of the sentence used to present emotive function in L’Oreal Paris advertisements. There were two theories applied in this study. The theory proposed by (Jakobson, 1980) applied to analyze the emotive function. Meanwhile, the theory proposed by (Quirk & Greenbaum, 1973) applied to analyze the elements of the sentence used to present emotive function in L’Oreal Paris advertisements. Observation method was applied in collecting the data of this study which was done by watching and note taking technique. In analyzing the data, descriptive qualitative and quantitative methods were applied. Formal and informal methods were also applied for presenting the findings. Based on the theories applied, there were 35 data of emotive function found in transcript of ten L’Oreal Paris advertisements videos which were presented with various combination of sentence elements.